A comparison of prebunking and debunking interventions for implied versus explicit misinformation. (29th December 2021) - Tay, Li Qian; Hurlstone, Mark J.; Kurz, Tim; Ecker, Ullrich K. H.
Abstract: Psychological research has offered valuable insights into how to combat misinformation. The studies conducted to date, however, have three limitations. First, pre‐emptive ("prebunking") and retroactive ("debunking") interventions have mostly been examined in parallel, and thus it is unclear which of these two predominant approaches is more effective. Second, there has been a focus on misinformation that is explicitly false, but implied misinformation that uses literally true information to mislead is common in the real world. Finally, studies have relied mainly on questionnaire measures of reasoning, neglecting behavioural impacts of misinformation and interventions. To offer incremental progress towards addressing these three issues, we conducted an experiment ( N = 735) involving misinformation on fair trade. We contrasted the effectiveness of prebunking versus debunking and the impacts of implied versus explicit misinformation, and incorporated novel measures assessing consumer behaviours (i.e., willingness‐to‐pay; information seeking; online misinformation promotion) in addition to standard questionnaire measures. In general, both prebunking and debunking reduced misinformation reliance. We also found that individuals tended to rely more on explicit than implied misinformation both with and without interventions.